Molecular Study of Antiviral Compound of Indonesian Herbal Medicine as 3CLpro and PLpro Inhibitor in SARS-COV-2 - Baiq Ressa Puspita Rizma; Yek Zen Mubarok; Dian Fathita Dwi Lestari; Agus Dwi Ananto (Acta Chimica Asiana, 2021)
Rapid transmission of COVID-19 disease and the fatal effects of the disease lead researchers to use various way to find potential anti-COVID-19 compounds, including using modern approaches. Molecular docking is one of the methods that can be used to analyse antiviral compounds and its molecular target from Indonesian herbs that are believed to have properties as anti-COVID-19. This study aims to analyse antiviral compounds from 5 herbs that have the potential as inhibitors of PLpro and 3CLpro, which both are a non-structural protein in SARS-CoV-2 by molecular docking approach using PLANTS. Remdesivir triphosphate, the active metabolite of remdesivir, was used as the comparison compound in studies. The results showed docking scores obtained from interactions between natural ligands, remdesivir trifospat, curcumin, demetoksikurkumin, bisdemetoksikurkumin, luteolin, apigenin, kuersetin, kaempferol, formononrtin-7-O-glucoronide, androgafolide, and neoandrogafolide with PLpro are as follows -111,441, -103,827, -103,609, -102,363, -100,27,-79,6655, -78.6901, -80.9337, -79.4686, -82.1124, -79.1789, and -97.2452.Combination between quercetin, neoandrographolide, bisdemethoxycurcumin, demetoxycurcumin, and curcumin showed a synergy effect by reduce its docking score. Meanwhile its interaction with the protein 3CLpro showed docking score for those compounds as follows 64.0074, -86.1811, -81.428, -87.1625, -78.2899, -73.4345,-70,3368, -71.5539, -68.4321, -72.0154, -75.9777 and -93.7746.Combination between andrographolide, neoandrographolide, bisdemethoxycurcumin, demetoxycurcumin and curcumin, also shows synegy effect in 3CLpro allow them to reduce the docking score.This study concludes that curcumin was known as the most potent compound that act as a PLpro inhibitor based on a docking score of -103,609, while in 3CLpro all the compound have a potential to inhibit 3CLpro with demethosxycurcumin and  neoandrogafolide as the most potent compound with a docking score -87,126 and -93.7746.